Village Leadership Synergy in Facing Development Challenges in Papua - Salmawati, Salmawati; Purnomo, Arie; Purwanti, Nanik; Ali, Muhammad; Refra, Mohamad Saleh (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to analyze how village leadership synergy can be a determining factor in facing development challenges in Papua. Using a qualitative approach and case study method, this study explores village leadership patterns, obstacles faced, and strategies that can be applied to strengthen inclusive and sustainable village development. The results of the study indicate that strong, collaborative, and community-based village leadership can increase development effectiveness. However, challenges such as limited infrastructure, less than optimal coordination, and human resource capacity that needs to be improved are still the main obstacles. Therefore, a more comprehensive strategy is needed, including increasing leadership training, more efficient budget allocation, and stronger support from local governments and related institutions. With closer cooperation between village heads, traditional leaders, and other stakeholders, development in Papua can run more effectively and sustainably. Community-based approaches and community empowerment must be the main priorities in village development policies. By actively involving the community in the planning and implementation process of development programs, it is hoped that the results achieved can be more in line with local needs and increase the sense of ownership and responsibility of the community towards the development of their village.